2001
DOI: 10.2307/3285174
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Depresses Innate and Acquired Resistance to Ticks in Natural Rodent Hosts: A Force for Aggregated Distributions of Parasites

Abstract: The effects of testosterone on acquired resistance to ticks, Ixodes ricinus, in their natural rodent hosts (voles, Clethrionomys glareolus, and wood-mice, Apodemus sylvaticus) were investigated by manipulating testosterone levels and exposing the hosts to repeated tick infestations. Testosterone reduced both innate and acquired resistance to tick feeding. During primary infestations, attachment rates were higher on rodents with high testosterone levels than on oil-implanted controls. Successive infestations on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
35
3
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 0 publications
7
35
3
1
Order By: Relevance
“…The infestation similarity between males and females coincides with the findings of Beldomenico et al (2004), but contrasts with the results obtained by Hughes and Randolph (2001), who showed experimental evidence that testosterone depresses the innate and acquired resistance to I. ricinus in rodents. Nevertheless, Lareschi (2000) found a marked preference of I. loricatus towards male hosts.…”
Section: Discussionsupporting
confidence: 44%
“…The infestation similarity between males and females coincides with the findings of Beldomenico et al (2004), but contrasts with the results obtained by Hughes and Randolph (2001), who showed experimental evidence that testosterone depresses the innate and acquired resistance to I. ricinus in rodents. Nevertheless, Lareschi (2000) found a marked preference of I. loricatus towards male hosts.…”
Section: Discussionsupporting
confidence: 44%
“…In our studies, rodents were not permitted to groom. Consequently, the main reason for better performance of fleas on male than on female hosts, at least at low RH, is likely due to gender differences in immunocompetence that stem from the higher level of androgens in males that compromise immune function (Folstad and Karter 1992;Hughes and Randolph 2001;Greives et al 2006, but see Vainikka et al 2004). A few experimental studies specifically aimed at testing the effect of host gender on feeding performance of fleas demonstrated that, indeed, fleas fed better on males than females (Haas 1965;Khokhlova et al 2009).…”
Section: Discussionmentioning
confidence: 95%
“…has been previously reported (L'Hostis et al 1996;Tälleklint and Jaenson 1997;Hanincova et al 2003;Michalik et al 2003;Stanko et al 2007) and could be due to a greater home range and a better roaming within the home range for Apodemus spp. (Tälleklint and Jaenson 1997;Le Louarn and Quéré 2003), and/or a better immunity against I. ricinus for M. glareolus (Dizij and Kurtenbach 1995;Hughes and Randolph 2001). The tendency (not signiWcant) to have a higher tick burden for M. arvalis than M. glareolus is surprising compared to other studies (L'Hostis et al 1996;Sinski et al 2006;Stanko et al 2007) and to the fact that M. arvalis was not found in woody vegetation and has a smaller home range (from 25 in winter to 500 m² in summer, Le Louarn and Quéré 2003).…”
Section: Discussionmentioning
confidence: 96%